A Reliability Game for Source Factors and Situational Awareness Experimentation - Francesca de Rosa; Anne-Laure Jousselme; Alessandro De Gloria (Serious Games Society, 2018)
Systems to support Situational Awareness take increasingly advantage of data and information fusion techniques. Due to the rise in the variety of information sources (e.g., sensors, open-source, intelligence, historical databases) and their possible lack of veracity those techniques should account for source reliability. Although the appropriate mathematical instruments exist, it still needs to be fully understood what are the factors that contribute to source reliability and what is their relative and total impact on Situation Assessment, which is the process that builds up Situational Awareness. In order to characterise source factors impact on human belief assessment the Reliability Game has been developed. This is a data exchange game in which the players are requested to perform Situational Assessment tasks by mentally processing incoming information and meta-information, abstracted and provided through cards. This paper presents the method, the design choices and shows through a qualitative analysis that the proposed approach is indeed able to capture elements of source factors impact on players' belief changes. Data collected through the game will be further analysed to inform and improve the design of information correction methods in multi-source information fusion systems.